The Influence of Social Experience on Student Character in the Digital Era - Alda Burhanuddin; Salsabila Nasution (Insight: Journal of Counseling and Psychology, 2025)
The transformation of social interaction from physical spaces to digital environments has created new and complex dynamics in the process of students’ character formation. This study aims to analyze the influence of peer interactions in the digital era on students’ morality and behavior, as well as to formulate relevant mitigation strategies. The study employed a literature review method by examining 15 scholarly articles and reference books published between 2018 and 2025. Data were analyzed using content analysis to synthesize patterns of relationships between digital interactions and changes in student character. The findings indicate that social media–based peer interaction has become a dominant agent of socialization, triggering the phenomenon of digital conformity. This condition contributes to character vulnerability, including the erosion of self-control, gadget addiction, and diminished empathy resulting from the normalization of cyber bullying. These findings suggest that conventional forms of supervision are no longer sufficient to counteract the negative impacts of online interactions. Therefore, this study recommends a reorientation of character education through the integration of digital literacy and the cultivation of internet ethics (netiquette) within school curricula to strengthen students’ moral resilience amid the global flow of information.